2004
DOI: 10.1073/pnas.0407290101
|View full text |Cite
|
Sign up to set email alerts
|

Haploinsufficiency of delta-like 4 ligand results in embryonic lethality due to major defects in arterial and vascular development

Abstract: Vascular development depends on the highly coordinated actions of a variety of angiogenic regulators, most of which apparently act downstream of vascular endothelial growth factor (VEGF). One potential such regulator is delta-like 4 ligand (Dll4), a recently identified partner for the Notch receptors. We generated mice in which the Dll4 gene was replaced with a reporter gene, and found that Dll4 expression is initially restricted to large arteries in the embryo, whereas in adult mice and tumor models, Dll4 is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

25
459
3
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 541 publications
(490 citation statements)
references
References 31 publications
25
459
3
3
Order By: Relevance
“…This is in accordance with previous in vivo data from Notch mutants, where endothelial cells do form but fail to remodel properly. 7,8 As was expected, inhibition of Notch signaling resulted in lower transcript levels of direct downstream genes Hey1 and Hey2 ( Figure 4B). Expression of the Notch ligand and arterial marker Dll4 decreased as did EphrinB2 levels, whereas expression of its receptor EphB4 remained unaltered at mRNA level.…”
Section: Inhibition Of Notch Signaling Overrides Vegf-driven Arterialmentioning
confidence: 61%
See 2 more Smart Citations
“…This is in accordance with previous in vivo data from Notch mutants, where endothelial cells do form but fail to remodel properly. 7,8 As was expected, inhibition of Notch signaling resulted in lower transcript levels of direct downstream genes Hey1 and Hey2 ( Figure 4B). Expression of the Notch ligand and arterial marker Dll4 decreased as did EphrinB2 levels, whereas expression of its receptor EphB4 remained unaltered at mRNA level.…”
Section: Inhibition Of Notch Signaling Overrides Vegf-driven Arterialmentioning
confidence: 61%
“…[7][8][9][10][11] To evaluate this, FACS sorted Flk1 ϩ cells were differentiated with or without ␥-secretase inhibitor (GSI) to block Notch signaling. Compared with control cultures, GSI treatment did neither alter CD31 and ␣SMA expression levels ( Figure 4A) nor the numbers of CD31 ϩ cells analyzed by FACS.…”
Section: Inhibition Of Notch Signaling Overrides Vegf-driven Arterialmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the Notch receptors, the loss of Notch1 proved to be the most deleterious to vascular development (Conlon et al, 1995;Krebs et al, 2000;Swiatek et al, 1994). Furthermore, several studies have demonstrated expression of Notch receptors and ligands in blood vessels and mural cells (Alva and Iruela-Arispe, 2004;Benedito and Duarte, 2005;Claxton and Fruttiger, 2004;Duarte et al, 2004;Gale et al, 2004;Shutter et al, 2000;Villa et al, 2001). These studies have also generally agreed that in addition to capillaries, Notch ligands and receptors are mostly confined to arteries, a finding that was subsequently supported by the requirement of Notch in establishing arterial identity through expression of EphrinB2 (Lawson et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…In terms of the ligands, only the loss of either Jag1 or Dll4 results in vascular defects, indicating that the other three Notch DSL ligands may not be as involved in vessel development. Notably, analysis of the phenotypes exhibited by Jag1 (Xue et al, 1999) and Dll4 (Duarte et al, 2004;Gale et al, 2004;Krebs et al, 2004) knockout mice, suggested that these two ligands are not functionally redundant. Indeed, the onset of lethality would indicate that each one of these molecules might provide a different array of signals through activation of Notch receptors.…”
Section: Resultsmentioning
confidence: 99%